Concise Neurology: a Focused Review - Espay, A. J. Alberto J. (Wolters Kluwer, 2021)
With easy-to-read, high-yield coverage of essential information in neurology, Concise Neurology: A Focused Review is a practical, everyday reference for busy practitioners, fellows, residents, and students who need a rapid overview of a complex subject. The second edition has been almost entirely rewritten to stay current with recent developments in the field but retains its quick-reference format: an intuitively designed one- or two-page presentation of each topic to facilitate rapid review. Virtually every topic of interest is covered, including the core concepts in diagnosis and treatment for each syndrome or disease. Material is presented in order of clinical relevance, maintaining a thematic unity across related pages for the most effective, efficient review. An engaging writing style offers many pearls and personal explanations from the authors that clarify difficult concepts. Every page offers a quick yet thoughtful summary of key points, making it particularly useful for busy residents, fellows, and ractitioners. Enrich Your Ebook Reading Experience!! Read directly on your preferred device(s),such as computer, tablet, or smartphone. Easily convert to audiobook,powering your content with natural language text-to-speech.